STUDY ON THE RATE OF REDUCTION OF Cr(VI) TO Cr(III) BY HUMIC ACID USING CONTINUM MULTICOMPONENT MODEL - Uripto Trisno Santoso; Herdiansyah Herdiansyah; Wega Trisunaryanti; Sri Juari Santosa (Universitas Gadjah Mada, 2004)
The objective of this study is to develop a rate equation for reduction of Cr(VI) by humic acid (HA) using a continuum multicomponent model. HA was extracted from peat soil samples in Gambut Subdistrict, South Kalimantan. Parameters influencing the rate of reduction, i.e., medium acidity ([H+]), as well as initial humic acid concentrations ([HA]o) and initial Cr(VI) concentrations ([Cr(VI)]o) were critically evaluated. Experiments were performed in triplicate tests. Aliquots of stock solution containing 100 mg/L HA were equilibrated for 24 h at pH 1.5, 2.05, 3.2, 5.6, and 6.5 before being spiked with 0.02 mM of Cr(VI). [Cr(VI)] was determined by 1,5-diphenylcarbazide spectrometric method. A similar set of rate experiments was conducted at a fixed pH of 1.5 and an [Cr(VI)]o of 0.02 mM and with [HA]o of 25, 50, 75, 100, 150, 200, and 250 mg/L. A third set of batch experiment was performed at pH 1.5, an [HA]o of 100 mg/L, and [Cr(VI)]o 0.01, 0.02, 0.05, 0.10, and 0.20 mM. The results showed that the rate of reduction cannot be adequately modeled by either a simple first- or second- order rate equation. A continum multicomponent model adequately describes the effect of solution parameters on the rates of Cr(VI) reduction.